Effects of Additional Visual Oscillation on Vection under Voluntary Eye Movement Conditions—Retinal Image Motion is Critical in Vection Facilitation. (May 2013) - Nakamura, Shinji
Horizontal oscillation introduced into a visual inducer can enhance an observer's illusory perception of vertical self-motion induced by a vertically moving optic flow pattern. To examine the effects of increased retinal image motion on the facilitation of vection, vection strength was analysed under various stimulus conditions where the oscillation of the retinal image was determined both by the motion of the visual stimulus and the observer's eye movements. The results indicated that the facilitation of vection was regulated by the oscillation of the visual stimulus on the observer's retina rather than the stimulus oscillation per se. Thus, the current experiment clearly favours the hypothesis that increased retinal image motion plays a critical role in the facilitation of vection.